A combined in vitro-in silico method for assessing the androgenic activities of bisphenol A and its analogues - Park, Chang Gyun; Adnan, Karim Md; Cho, Hyunki; Ryu, Chang Seon; Yoon, Juyong; Kim, Young Jun (Toxicology in vitro, 2024)
Interactions between endocrine-disruptor chemicals (EDCs) and androgen receptor (AR) have adverse effects on the endocrine system, leading to human reproductive dysfunction. Bisphenol A (BPA) is an EDC that can damage both the environment and human health. Although numerous BPA analogues have been produced as substitutes for BPA, few studies have evaluated their endocrine-disrupting abilities. We assessed the (anti)-androgenic activities of BPA and its analogues using a yeast-based reporter assay. The BPA analogues tested were bisphenol S (BPS), 4-phenylphenol (4PP), 4,4′-(9-fluorenyliden)-diphenol (BPFL), tetramethyl bisphenol F (TMBPF), and tetramethyl bisphenol A (TMBPA). We also conducted molecular docking and dynamics simulations to assess the interactions of BPA and its analogues with the ligand-binding domain of human AR (AR-LBD). Neither BPA nor its analogues had androgenic activity; however, all except BPFL exerted robust anti-androgenic effects. Consistent with the in vitro results, anti-androgenic analogues of BPA formed hydrogen bonding patterns with key residues that differed from the patterns of endogenous hormones, indicating that the analogues display in inappropriate orientations when interacting with the binding pocket of AR-LBD. Our findings indicate that BPA and its analogues disrupt androgen signaling by interacting with the AR-LBD. Overall, BPA and its analogues display endocrine-disrupting activity, which is mediated by AR.